Predictors of homelessness among families and single adults after exit from homelessness prevention and rapid re-housing programs: evidence from the Department of Veterans Affairs Supportive Services for Veteran Families Program - Byrne, Thomas H. (Housing policy debate, 2015)
This article assesses the extent and predictors of homelessness among Veterans (both Veterans in families with children and single adults Veterans) exiting the Supportive Services for Veteran Families (SSVF) program, which is a nationwide homelessness prevention and rapid re-housing program geared primarily towards those experiencing crisis homelessness. Among rapid re-housing participants, 16% and 26% of single adult Veterans experienced an episode of homelessness at one and two years post-SSVF exit; the comparable figures at those follow-up times for Veterans in families were 9.4% and 15.5%, respectively. Relatively fewer single adult Veterans and Veterans in families receiving homelessness prevention services experienced an episode of homelessness at one and two years post-SSVF exit. Veteran-level characteristics, including age, gender, prior history of homelessness and recent engagement with VA healthcare were generally more salient predictors of homelessness following SSVF exit than variables measuring SSVF program factors, or community-level housing market conditions.U.S. Department of Veterans Affairs, National Center on Homelessness Among Veteran